Learning from Other's Mistakes - One Approach to teaching Information Literacy - MacDonald, Ewen; Saarti, Jarmo (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
Everyone in the academic community is today confronted with an unprecedented problem. One click of the mouse can provide a student with enough source material to construct a doctoral thesis. Thus, the problem is no longer to locate the relevant material; today the difficulty is in separating the wheat from the chaff, or a more apt analogy, finding the few gold nuggets in the mountains of dross. The information literate student has to be able to evaluate web-based material which may be opinion disguised as fact. In this article we describe a short course entitled ‘Critical Journal Club’ and how after participating in this course, students become more critical, more sceptical and more information literate. The number of journals has increased and the standard of refereeing is now more inconsistent than ever. In particular, one critical change has been the move from print to electronic formatting. This means that few journals employ sub-editors with a scientific background - instead articles are transmitted in pdf-format directly to the publisher. It is important that students are made aware that even material in eminent journals can occasionally contain substantial errors as well as numerous grammatical mistakes. We aim to stimulate discussion on the current level of peer reviewing as well as stressing the importance of integrating critical information literature skills into the curriculum.